Primary Open-Angle Glaucoma Patients in the Ophthalmology Outpatient Clinic Dr. Soetomo General Academic Hospital, Surabaya, in 2013–2015 - Rasyda, Risnanda Putri; Wahyuni, Indri; Sari, Dewi Ratna (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: POAG is a common type of glaucoma. POAG patients were predominantly >60 years old, with males being more dominant than females.   Abstract Introduction: Primary open-angle glaucoma (POAG) is a progressive, chronic optic neuropathy characterized by distinct optic nerve atrophy and impairment of the visual field. The purpose of this study was to describe the characteristics of primary open-angle glaucoma patients in the ophthalmology outpatient clinic of Dr. Soetomo General Academic Hospital, Surabaya, in 2013–2015. Methods: This was a descriptive-retrospective study. Samples were patients with a primary open-angle glaucoma (POAG) diagnosis in the ophthalmology outpatient clinic at Dr. Soetomo General Academic Hospital, Surabaya, in 2013–2015. Results: There were 88 samples of POAG patients in the ophthalmology outpatient clinic at Dr. Soetomo General Academic Hospital, Surabaya, in 2013–2015. POAG was dominated in the age group 60–69 years old, with a percentage of 37.50%. Males were more dominant than females, with a percentage of 55.70%. Many POAG patients were unemployed, with a percentage of 56.82%. Most patients with POAG did not have a history of hypertension or diabetes mellitus, with a percentage of 73.86%. Patients who had a history of hypertension were 11.36%, those with diabetes mellitus were 9.09%, and those who had a history of both hypertension and diabetes mellitus were 5.68%. Conclusion: POAG was a higher risk in older adults, with males being more dominant than females. Most patients did not have a history of either hypertension or diabetes mellitus.